2016
DOI: 10.1021/acs.jpclett.6b01642
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Dynamics and Intramolecular Charge Transfer in the S2 (11Bu+) Excited State of Peridinin: A Mechanism for Enhanced Mid-Visible Light Harvesting

Abstract: Of the carotenoids known in photosynthetic organisms, peridinin exhibits one of the highest quantum efficiencies for excitation energy transfer to chlorophyll (Chl) a acceptors. The mechanism for this enhanced performance involves an order-of-magnitude slowing of the S2 (1(1)Bu(+)) → S1 (2(1)Ag(-)) nonradiative decay pathway compared to carotenoids lacking carbonyl substitution. Using femtosecond transient grating spectroscopy with optical heterodyne detection, we have obtained the first evidence that the nonr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 51 publications
5
55
0
Order By: Relevance
“…[18] However, involvement of another dark intermediate state has also been invoked. The nature of this state, usually denoted as the S x state, is still unknown and either a separate electronic state of B u À symmetry [11,19,20] or a twisted S 2 state [21,22] have been proposed as the intermediate state facilitating the S 2 -S 1 relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…[18] However, involvement of another dark intermediate state has also been invoked. The nature of this state, usually denoted as the S x state, is still unknown and either a separate electronic state of B u À symmetry [11,19,20] or a twisted S 2 state [21,22] have been proposed as the intermediate state facilitating the S 2 -S 1 relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this framework ignores the unique chemical nature of the peridinin Car-containing an allene tail and a lactone ring-that may support intramolecular-charge-transfer (ICT) character and even a separate ICT state [20]. Yet much like the claims of spectral evidence for dark intermediate states, the nature of ICT in peridinin remains controversially assigned, as evidenced by twenty-first-century experimental [21][22][23] and computational [24][25][26][27] investigations. On one hand, red-shifted emission with diminished lifetime in the face of polar solvent [20] and a distinct low-lying electronic excited state with ICT character [24] have been reported; on the other hand, conformational bright-state local minima [21,22] and bond-vibration-driven interplay between the lowest-lying bright-and dark-state properties [25] have been proposed as explanations for peridinin's anomalous photophysics.…”
Section: Introductionmentioning
confidence: 99%
“… 42 45 Moreover, the 10 fs time resolution achieved by this technique is essential to investigate with better detail the ultrafast dynamics subsequent to S 2 excitation, expected to be in the sub-100 fs time range. 26 , 28 , 46 , 47 …”
mentioning
confidence: 99%
“…This picture seems to be also supported by the work of Ghosh et al, who identified a <20 fs nonradiative decay of the S 2 of peridinin to an S x state with a strong ICT character, assigned to a distorted configuration. 47 , 57 …”
mentioning
confidence: 99%
See 1 more Smart Citation